2021
DOI: 10.1177/15593258211059317
|View full text |Cite
|
Sign up to set email alerts
|

What Would Become of Nuclear Risk if Governments Changed Their Regulations to Recognize the Evidence of Radiation’s Beneficial Health Effects for Exposures That Are Below the Thresholds for Detrimental Effects?

Abstract: The 1953 Atoms for Peace Speech to the United Nations proposed applying nuclear energy to essential needs, including abundant electrical energy. The widespread fear of ionizing radiation from nuclear facilities and medical procedures began after the United States National Academy of Sciences performed a study of radiation dangers to the human genome. This study, initiated and managed by an oil industry benefactor, recommended in 1956 that the risk of radiation-induced mutations be assessed using the linear no-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 19 publications
0
24
0
1
Order By: Relevance
“…Low doses are only for diagnostic imaging, and each exposure must now be as low as reasonably achievable, to minimize the hypothetical risk of radiation-induced cancer, still calculated by the LNT model. 5 , 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low doses are only for diagnostic imaging, and each exposure must now be as low as reasonably achievable, to minimize the hypothetical risk of radiation-induced cancer, still calculated by the LNT model. 5 , 18 …”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 Studies by the lead author on the Hiroshima atomic bomb survivors have revealed the acute threshold dose for the onset of radiation-induced leukemia to be quite high, about 1.1 Gy. 5 , 18 …”
Section: Discussionmentioning
confidence: 99%
“…The 32 700 survivors in the low-dose zone, whose exposures were below this threshold, had a lower-thannormal incidence of leukemia. 1 In 1959, the NCRP adopted the precautionary principle policy, which, in effect, meant that the LNT model would be employed to estimate the risk of radiation-induced cancer. This decision, published in 1960, was based on public fear and lack of knowledge.…”
Section: Ldr Exposure Policy and Public Perceptionsmentioning
confidence: 99%
“…It has long been known that the public has concern in relation to radiation exposure, that is not shared with nuclear experts. 1 These concerns include that all radiation exposures (including X-rays) are harmful (i.e., carcinogenic), radiation exposures are cumulative within our body, and children are more susceptible to radiation. 2 A common thread between problems of radiation worker exposure during cancer treatment and keeping health care workers in these areas safe is the issue of exposure to low-dose radiation (LDR) (defined as below 100 mSv (the radiation protection policy definition.…”
Section: Introductionmentioning
confidence: 99%
“…The main basis for cancer risk quantification for humans exposed to low radiation doses is epidemiologic studies. Findings from such studies have influenced the development of the current system of radiological protection along with the related radiation-dose-reducing concept 1 “As Low As Reasonably Achievable (ALARA).” Cancer risk quantification for low radiation doses is mainly based on the controversial 2 linear-no-threshold (LNT) model which is unsupported 3 by modern radiation biology. There are uncertainties with any cancer risk assessment related to radiation exposure.…”
mentioning
confidence: 99%